تحليل الخطاب القرآني في ضوء مناهج التفسير - التفسير الكبير أنموذجا- - مفلاح بن عبد الله (My University, 2009)
The correlation between the text and the interpretation is adjusted according to two major paradigms: the former is reflected by a trust that language is no more than a representation of the writer’s spirit and the spirit of the time. The latter is that there is a certain fusion between the text and the writer, the writer and the reader, and the pieces of the text itself so as all of the text, the writer and the reader, become prospects for a single image. It is worth mentioning that the human being in fact moves in an infinite orbit of interpretations, and not in an orbit of signs which internal and external subsistence could be close to some interpretation’s transactions, and it is in reality assessments for the mind’s part in what it perceives as signs varying according to the different occasions and contexts, something that gives potential to this statement to end the disagreement around the dichotomy of Text/ Interpretation to make both parts of the dichotomy two faces of the same coin, for the reason that there is no text to be interpreted but there is an interpretation to be reinterpreted. Thus, methodology and the real world seem to be in contradiction in many contexts, each wants to control the other on the level of definition or description, a matter that makes the majority of interpreters pay closer attention to the case of dichotomy gathering such propositions, that they are dichotomies which do fit to go with the nature of the speech act, on the principle that the speaker sees the interaction from a double single angle. As long as he knows perfectly that his existentialist and cognitive judgments are connected to the receiver’s horizon in shape and content, and that is what makes communication a give and take; both speaker and hearer need each other. It is an effort to unravel the problem posed already in the past in the form of a reflection we think it is capable to take a generous share to embark in, and adopt this rationale, what pushed us to call it as it fellows: Coranic Discourse in the light of interpretation methods» The Greatest Interpretative Sample” To understand the problematic of explanation and interpretation in the Islamic heritage, one should make the difference between two readings experiments for the coranic discourse represented by two generations of interpreters; the first of them was satisfied with the single meaning of two terms and treated them on the basis of synonymy. However, the second generation put the terms apart according to the text and the opinion. Thus, in a quest for meaning, the interpretation of Coran (7th verse of Aal Omraan) had been the precursor for a renewal of paradigms of interpretation. Indeed Fakhr Arrazi’s readings obey different methods and practical manipulations, all of which based on the rationalist proof. His work, conscious of its limitations related to his impotency next to the perfect and absolute Coran, he refers to reason as the efficient tool and the measure to guarantee and serve the truth. He exploited the Arabic heritage with its various cultures and philosophies and framed an important background on which the interpretation of the coranic text could benefit extensively.